2018
DOI: 10.1039/c8nr00648b
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption of silicon on an iridium surface ruling out silicene growth

Abstract: The adsorption of Si atoms on a metal surface might proceed through complex surface processes, whose rate is determined differently by factors such as temperature, Si coverage, and metal cohesive energy. Among other transition metals, iridium is a special case since the Ir(111) surface was reported first, in addition to Ag(111), as being suitable for the epitaxy of silicene monolayers. In this study we followed the adsorption of Si on the Ir(111) surface via high resolution core level photoelectron spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…For instance, there have been numerous reports of adsorbed Si atoms diffusing through and intercalating between thin films and substrates. [28][29][30] We suspect that a similar process is at play during this deposition. In particular, we hypothesize that during Nb deposition, a few layers of Si atoms continuously float to the top surface in an effort to reduce the surface free energy of the system.…”
Section: Methodsmentioning
confidence: 80%
“…For instance, there have been numerous reports of adsorbed Si atoms diffusing through and intercalating between thin films and substrates. [28][29][30] We suspect that a similar process is at play during this deposition. In particular, we hypothesize that during Nb deposition, a few layers of Si atoms continuously float to the top surface in an effort to reduce the surface free energy of the system.…”
Section: Methodsmentioning
confidence: 80%
“…However, abstraction processes on graphene are known to heat locally the substrate, because of the release of the puckering energy that is left on the substrate upon H 2 molecule formation, and thus might contribute to enhance the adatom mobility. Furthermore, some surface diffusion is possible for nonthermal H adatoms that may form upon impact with graphene when the adsorption energy is efficiently channeled into translational energy along the surface, , as it may happen when light projectiles impinge on corrugated surfaces . These hot-atom species, commonly found when H interacts with bare metal surfaces, are able to travel for long distances from their formation point and can thus reach Gr defects and diffuse underneath graphene.…”
Section: Resultsmentioning
confidence: 99%
“…46,47 There again, strong interactions with the substrates were demonstrated both theoretically and experimentally. 48,49 More recently, to overcome this limitation various experiments have been carried out on C-based inert substrates such as highly oriented pyrolytic graphite (HOPG) with hexagonal atomic arrangements. [50][51][52][53] On this substrate, the results demonstrated that the charge modulations caused by quantum interferences (QI) serve as templates and guide the incoming Si atoms to self-assemble in 2D clusters.…”
Section: Introductionmentioning
confidence: 99%